Efficient conversion of carbohydrates into 5-hydroxylmethylfurfan and 5-ethoxymethylfurfural over sufonic acid-functionalized mesoporous carbon catalyst. (15th March 2017) - Wang, Junmei; Zhang, Zehui; Jin, Shiwei; Shen, Xizhou
Highlights: Sulfonic acid-functionalized mesoporous carbon (OMC-SO3 H) was prepared. It is an effective acid catalysts for the synthesis of HMF and EMF. A high HMF yield of 89.4% was obtained from fructose at 120 °C within 30 min. The one-pot conversion of fructose based carbohydrates can generate EMF yield around 55%. The catalyst was stable and could be reused. Abstract: Catalytic conversion of carbohydrates into valuable chemical and liquid fuels has received considerable attention in recent years. In this study, sulfonic acid-functionalized ordered mesoporous carbon (OMC-SO3 H) was prepared and well characterized by physical techniques such as TEM, nitrogen physisorption measurements and XRD. The as-prepared OMC-SO3 H was then used for the acid-catalyzed conversion of fructose based carbohydrates into 5-hydroxylmethylfurfan (HMF) or 5-ethoxymethylfurfural (EMF). Due to the high surface area and high acidity, the OMC-SO3 H catalyst showed a comparable catalytic performance as the homogeneous catalysts. The dehydration of fructose over the OMC-SO3 H catalyst produced a high HMF yield of 89.4% in DMSO at 120 °C within 30 min. The one-pot transformation of fructose carbohydrates were also smoothly performed, affording EMF yields of 55.7%, 53.6% and 26.8% from fructose, iuline and sucrose after 24 h at 140 °C, respectively. Furthermore, the OMC-SO3 H catalyst can be reused and no apparent loss of the activity was observed.